Performan reproduksi pada persilangan Kambing Boer dan Peranakan Etawah (PE) - F. Parasmawati; Suyadi Suyadi; Sri Wahyuningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The study tends to evaluate the reproductive performances of Boer x PE goats crossbred in field laboratory “Sumber Sekar” of the Faculty of Animal Husbandry, Brawijaya University. Data covered the reproductive performance from 2010 – 2012 including data from 23 multipaorous does (11 does of pure Boer goats, 12 does of Boer x PE crossbred). The results shows that service per conception (S/C) of the pure Boer was 3.09 ± 1.57 and 2.75± 1.35 for the crossbred (P>0.05). The days open (DO) of the Boer goat was 202.71 ± 95.56 days this was not significantly difference to the crossbred goats (208.04 ±137.51days). The kidding interval (316.84 ± 125.64 days vs. 360.45 ± 148.96 days) and the litter size (1.78 ±0.71 vs. 1.70 ± 0.86) were not significantly difference (P>0.05) between the respective groups. In conclusion, the crossing program between male Boer goats and male PE does did not influence the reproductive performances in both goats (pure Boer goats and their crosses with local PE goats). Key words: litter size, service per conception, days open, kidding interval, litter size